2018
DOI: 10.21608/adjalexu.2018.58004
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Self-Adhering Flowable Composite Resin as a Pit and Fissure Sealant

Abstract: INTRODUCTION: The success of pit and fissure sealant is highly dependent on obtaining and maintaining an intimate adaptation to the tooth surface. Self-adherable flowable composite (Vertise Flow) represents a new generation of dental materials that combines the properties of flowable composites and self-adhesives. OBJECTIVES: The aim of this study was to evaluate the Vertise Flow (VF) in term of shear bond strength and sealing ability to enamel of pit and fissure in comparison to conventional sealant with self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…On the other hand, this study agrees with Owida et al, 2018 who concluded that Vertise Flow have significantly higher retention, bond strength and better sealing ability to pits and fissures when compared to Clinpro sealant (resin based sealant with fluoride, 3M ESPE,USA) (19) . The high bond strength of Vertise Flow due to Opti-Bond technology (All in one) that incorporating etching adhesive and priming.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, this study agrees with Owida et al, 2018 who concluded that Vertise Flow have significantly higher retention, bond strength and better sealing ability to pits and fissures when compared to Clinpro sealant (resin based sealant with fluoride, 3M ESPE,USA) (19) . The high bond strength of Vertise Flow due to Opti-Bond technology (All in one) that incorporating etching adhesive and priming.…”
Section: Resultssupporting
confidence: 91%
“…To get rid of these problems, a self-adhering resin(SAR) based fissure sealants were developed. The resin in these fissure sealants is a self-adhesive flowable composite that's used in the resto- ous acid etching or bond placement with high enamel bonding property (7) (19) .…”
Section: Introductionmentioning
confidence: 99%
“…This result was in accordance with Korporowicz et al, 2019 (9) who reported that self-adhesive flowable composite after enamel etchant was statistically significantly higher than that of the conventional pits and fissures sealant. Also, a previous study reported that acid etching was still mandatory with a self-adhering flowable resin composite to improve retention and obtain better sealing ability compared to resin based sealant (18) . The results of the bonded groups with Single Bond Universal adhesive (Group III and Group V) showed the highest microshear bond strength values.…”
Section: Discussionmentioning
confidence: 99%